Homogenization, lyophilization or acid-extraction of meat products improves iron uptake from cereal-meat product combinations in an in vitro digestion/Caco-2 cell model - Pachón, Helena; Stoltzfus, RJ; Glahn, Raymond P. (Cambridge University Press, 2008)
The effect of processing (homogenization, lyophilization, acid-extraction) meat products on iron uptake from meat combined with uncooked iron-fortified cereal was evaluated using an in vitro digestion/Caco-2 cell model. Beef was cooked, blended to create smaller meat particles, and combined with electrolytic iron-fortified infant rice cereal. Chicken liver was cooked and blended, lyophilized, or acid-extracted, and combined with FeSO4-fortified wheat flour. In the beef–cereal combination, Caco-2 cell iron uptake, assessed by measuring the ferritin formed by cells, was greater when the beef was blended for the greatest amount of time (360 s) compared with 30 s (P < 0·05). Smaller liver particles (blended for 360 s or lyophilized) significantly enhanced iron uptake compared to liver blended for 60 s (P < 0·001) in the liver–flour combination. Compared to liver blended for 60 s, acid-extraction of liver significantly enhanced iron uptake (P = 0·03) in the liver–flour combination. Homogenization of beef and homogenization, lyophilization, or acid-extraction of chicken liver increases the enhancing effect of meat products on iron absorption in iron-fortified cereals.